Transbronchial cryobiopsy in diffuse parenchymal lung disease. A new star in the horizon - Poletti, Venerino; Benzaquen, Sadia (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
IntroductionSurgical lung biopsy is still considered the gold standard to obtain enough lung tissue in the clinical context of diffuse parenchymal lung disease...